The Technology-Based Arabic Language Learning: An Analysis of the Experiences, Adaptations, and Perceptions of PBA Students at STAIN Bengkalis - Marhamah Ulfa; Dian Ratna Suri; Ahmad Nurul Huda Salmas (Al-Himam, 2025)
This study explores the transformation of Arabic language learning through technology-based media at STAIN Bengkalis, particularly within the Arabic Language Education Study Program. Employing a qualitative approach with a phenomenological design, this research focuses on students’ lived experiences in engaging with technology-integrated learning environments. Data were collected through in-depth interviews, participatory observation, and documentation, involving students who have previously taken part in technology-supported learning activities. The findings indicate that students generally hold positive perceptions toward the use of digital platforms such as Canva, Kahoot, CapCut, and Quizizz, as these tools enhance engagement, interactivity, and learning motivation. The integration of such media is perceived to make the learning process more dynamic and student-centered, contributing to improved comprehension and participation. Nevertheless, the implementation of technology-based learning also encounters several constraints, including limited access to adequate devices, unstable internet connectivity, and restricted data quotas, all of which can disrupt the continuity of learning. Despite these challenges, the study concludes that technology exerts a significantly positive influence on Arabic language learning. Strengthening institutional support through improved technological facilities and systematic training for both students and lecturers is recommended to optimize the effectiveness of digital-based learning in the future.